2018
DOI: 10.1111/cico.12327
|View full text |Cite
|
Sign up to set email alerts
|

Eclipsing Community? Neighborhood Disadvantage, Social Mechanisms, and Neighborly Attitudes and Behaviors

Abstract: This study investigates how objective neighborhood characteristics influence attitudinal and behavioral dimensions of community social organization. Grounded in ecological and neighborhood effects traditions, I extend prior inquiries by adjudicating the social mechanisms that link neighborhood disadvantage with residents' satisfaction and neighboring. Results from longitudinal data from the Los Angeles Family and Neighborhood Survey indicate that the neighborhood disadvantage perspective garners support when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(243 reference statements)
0
8
0
Order By: Relevance
“…Neighbourhood satisfaction [50] was assessed by asking, "All things considered, would you say you are very satisfied, satisfied, dissatisfied, very dissatisfied or neutralneither satisfied nor dissatisfied, with your neighbourhood as a place to live?" Others have used this single item question to understand residents'overall perceptions of their neighborhood [51][52][53][54]. This item was dichotomized with the highest two levels (satisfied or very satisfied coded as 1, and neutral, dissatisfied or very dissatisfied coded as 0) .…”
Section: Methodsmentioning
confidence: 99%
“…Neighbourhood satisfaction [50] was assessed by asking, "All things considered, would you say you are very satisfied, satisfied, dissatisfied, very dissatisfied or neutralneither satisfied nor dissatisfied, with your neighbourhood as a place to live?" Others have used this single item question to understand residents'overall perceptions of their neighborhood [51][52][53][54]. This item was dichotomized with the highest two levels (satisfied or very satisfied coded as 1, and neutral, dissatisfied or very dissatisfied coded as 0) .…”
Section: Methodsmentioning
confidence: 99%
“…One such resource, neighborhood ties (also referred to as “network interaction” and/or “reciprocated exchange”; Browning, Dirlam, and Boettner 2016) captures the extent to which community members engage in what Sharp (2018) calls “neighboring.” Neighboring includes behaviors such as doing favors for other residents, watching over one another’s property, asking each other for advice, and getting together in the community to socialize. In communities with stronger neighborhood ties, parents are more likely to know other parents, talk to other parents about the local youth, and intervene on behalf of other parents’ children.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Length of time lived in a school district also influences racial attitudes through its influence on attachment and entitlement (Sharp, 2018; Torunczyk-Ruiz & Martinovic, 2020). Scholars testing community attachment models found that living longer in one area leads to greater amounts of neighboring—which is “the extent to which neighbors do favors for each other, watch over each other’s property, and talk to and ask one another for advice” (Sharp, 2018, p. 628). Longer-term residents also tend to feel more entitled to making sure that neighborhood is protected and improved (Torunczyk-Ruiz & Martinovic, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%